Problems of Vegetable Producing Farmers in Erode, Coimbatore and Tiruppur Districts of Tamil Nadu - Saravanan, S. (Indian Journal of Marketing, 2012)
The farmers, who produce crops, struggle a lot to bring them up. They plough and till the land, seed the plants, water resources, clean and pack the produce, ready to be taken to the markets for sale. Even at the time of producing the crops, and at the time of selling them, they face a lot of hurdles and obstacles such as the interference of brokers and middlemen, lack of insurance facility, lack of finance, high cost of inputs, problems related to storage of the produce and transportation problems. In the market, the farmers are cheated by the brokers when the purchase is being made - like charging a low price for the produce, weighing the produce in faulty machines and so on. Thus, the farmers face a number of problems from the initial stage of production till the sale of the produce in the market. The present research was carried out with the aim of ascertaining the socio-economic conditions and various problems faced by the vegetable cultivating farmers of the Erode, Coimbatore and Tiruppur districts of the state of Tamil Nadu.